2018
DOI: 10.1177/0265407518802451
|View full text |Cite
|
Sign up to set email alerts
|

Inducing jealousy and intimate partner violence among young adults

Abstract: Jealousy has been linked to a number of deleterious relationship outcomes; yet, few studies have explored the broader ways in which inducing jealousy affects intimate relationships. Using data on 892 young adults from the Toledo Adolescent Relationships Study, we examined correlates and consequences of intentionally inducing jealousy in intimate relationships. Results indicated that factors both unique and internal to the intimate dyad and those external to the intimate relationship were associated with jealou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 41 publications
0
18
0
1
Order By: Relevance
“…Adding to the complexity, research on IPV indicates that, during adolescence and young adulthood, relationship duration is generally positively related to IPV (Kaufman-Parks et al, 2019). This is another potentially important basic finding, as it suggests that overall attitudes such as men's adherence to traditional gender role ideologies does not completely account for the differential patterning of serious conflicts and IPV over the course of a relationship.…”
Section: Incorporating Women's Perspectives and Actions Into Research/program Contentmentioning
confidence: 99%
See 3 more Smart Citations
“…Adding to the complexity, research on IPV indicates that, during adolescence and young adulthood, relationship duration is generally positively related to IPV (Kaufman-Parks et al, 2019). This is another potentially important basic finding, as it suggests that overall attitudes such as men's adherence to traditional gender role ideologies does not completely account for the differential patterning of serious conflicts and IPV over the course of a relationship.…”
Section: Incorporating Women's Perspectives and Actions Into Research/program Contentmentioning
confidence: 99%
“…For example, results based on TARS have shown that infidelity of one partner is a significant correlate of infidelity of the other partner (Giordano et al, 2015). In addition, a recent analysis showed that if one partner engages in actions that fit under the rubric of jealousy induction (trying to make the other partner jealous), this is also significantly related to the odds that the other partner will engage in these forms of behavior (Kaufman-Parks et al, 2019). Importantly, Kaufman-Parks et al (2019) documented that the use of these jealousy induction strategies was significantly linked to self-reports of IPV.…”
Section: Gender and Infidelitymentioning
confidence: 99%
See 2 more Smart Citations
“…Por atravessar diferentes épocas da história do ser humano, algumas manifestações de ciúmes podem ser consideradas familiares, percebidas como opositoras da apatia; valorizadas socialmente; ou ainda, tratadas como sinônimo de amor, não obstante, podem mascarar ações abusivas (Almeida & Lourenço, 2011;Baroncelli, 2011;Wright, 2017). Acerca disso, uma evidência bastante recorrente empiricamente é a de que o ciúme pode se apresentar como um importante gatilho para atos violentos dentro dos relacionamentos amorosos; ou ainda, a sua manifestação pode vim acompanhada de ameaças, agressões físicas e verbais (Daspe, Vaillancourt-Morel, Lussier, & Sabourin, 2018;Kaufman-Parks, Longmore, Giordano, & Manning, 2018;Wright, 2017).…”
Section: Análise Prototípicaunclassified